Rhetoric and the Humanities: New Perspectives on Culture, Arts, and the Media (KULT_online, 2013)
In his 2013 monograph Modern Rhetoric in Culture, Arts, and Media (de Gruyter), Joachim Knape develops a modern theory of rhetoric that sheds light on the communicative and cultural aspects that have thus far been neglected by scholars of rhetoric. Knape concentrates on selected fields of application (literature, music, graphics, feature films) that allow him to demonstrate that rhetorical studies are of increasing relevance for the humanities and for society more generally. Though Knape’s work is firmly grounded in rhetorical approaches, his book opens up portals for dialogue between rhetoric and poetics as well as between rhetoric and visual studies or media theory, to name but a few examples. Knape’s case studies can thus serve as starting points for further research on goal-directed and strategic communication across the disciplines.